2013
DOI: 10.2308/isys-50563
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Business Value of Business Intelligence: The Role of Shared Knowledge and Assimilation

Abstract: Business intelligence (BI) systems have attracted significant interest from senior executives and consultants for their ability to exploit organizational data and provide operational and strategic benefits through improved management control systems. A large body of literature indicates that organizations have largely failed to use their business intelligence investments effectively to exploit the wealth of data they capture in their ERP systems. As a result, BI has too often failed to support organizations' m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 39 publications
2
64
0
2
Order By: Relevance
“…BI systems use analytics and enterprise system databases. As a result, BI systems failed to support managerial decision making at both the strategic and operational levels, and hence failing to create business value through BI investments [17,18]. This empirical study found evidence for the importance of BI systems assimilation and the need for shared domain knowledge at the strategic and operational levels as the drivers of BI business value.…”
Section: Predictive Analytics and Decision-making Effectivenessmentioning
confidence: 85%
“…BI systems use analytics and enterprise system databases. As a result, BI systems failed to support managerial decision making at both the strategic and operational levels, and hence failing to create business value through BI investments [17,18]. This empirical study found evidence for the importance of BI systems assimilation and the need for shared domain knowledge at the strategic and operational levels as the drivers of BI business value.…”
Section: Predictive Analytics and Decision-making Effectivenessmentioning
confidence: 85%
“…Accordingly, we suggest that under certain situations, a single integrated data structure may be beneficial, whereas in other situations it is not necessarily appropriate (c.f. Balkan and Goul, 2010;Elbashir et al 2013). Specifically, if the company has a day-to-day need to update forecasts for production planning purposes and focuses on forecasting non-monetary figures, then integration is perhaps unjustified from a cost-benefit point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it can be argued that BI systems have emerged to solve the problem of providing flexibility of use while ensuring the integration of data. In fact, Elbashir et al (2013) argue that BI systems only create value for business when they are integrated effectively with data warehouses of organisations. Further, they suggest that, ideally the BI system should be configured to provide analysis and reporting that can then be effectively used both in decision-making and managerial control.…”
Section: Introductionmentioning
confidence: 99%
“…Firm size is used as a proxy for the resource base of the organization that may influence the integrative value and firm performance [45]. Time since both systems where integrated was included to measure the knowledge and experience that organizations obtain from working overtime [45].…”
Section: Controlsmentioning
confidence: 99%